A systematic literature review of colorectal robotic surgery with the Hugo robotic-assisted surgery (RAS) system: feasibility, safety, and clinical applications - Filippo Carannante; Kiara Sejfullai; Valentina Miacci; Guglielmo Niccolò Piozzi; Gianluca Costa; Jim S. Khan; Marco Caricato; Gabriella Teresa Capolupo (Annals of Coloproctology, 2026)
Purpose: The Hugo robotic-assisted surgery (RAS) system is a novel modular robotic platform that has recently been introduced in colorectal surgery. Although robotic approaches have improved surgical ergonomics and precision, evidence specific to the Hugo RAS system remains limited. This systematic review synthesizes the current literature on colorectal procedures performed with the Hugo RAS system and evaluates feasibility, safety, and early oncologic outcomes.Methods: A systematic literature search of PubMed, Scopus, Embase, and Ovid was conducted through September 2025 in accordance with the PRISMA 2020 guidelines. Eligible studies included case series, cohort studies, and comparative analyses that reported perioperative or oncologic outcomes of colorectal procedures performed using the Hugo RAS system.Results: Thirteen studies were included and encompassed right and left hemicolectomies, rectal resections, and total colectomies. The median docking time was 7.5 minutes (range, 5–18 minutes), the median operative time was 225 minutes (range, 163–632 minutes), the conversion rate was 3.6%, and the mean hospital stay was 5.6 days. The overall complication rate was 11%, and most complications were Clavien-Dindo grade I–II. Perioperative and oncologic outcomes, including lymph node yield, total mesorectal excision quality, and circumferential resection margin status, were comparable to those reported for laparoscopy. Reported advantages included modular arm flexibility, an ergonomic open-console design, and stable visualization, whereas reported limitations included setup time and arm bulkiness.Conclusion: The available evidence supports the feasibility and safety of the Hugo RAS system in colorectal surgery, with outcomes broadly comparable to those of laparoscopy; however, the evidence remains limited by study heterogeneity, the absence of randomized trials, and reliance mainly on small retrospective series. The platform offers potentially useful ergonomic and technical features, but multicenter prospective studies with larger cohorts, long-term follow-up, and cost-effectiveness analyses are needed to define its role in oncologic colorectal surgery.Trial registration: The protocol was registered in PROSPERO (No. CRD420251028698).